Aquaculture subsidies in the European Union: Evolution, impact and future potential for growth. (June 2019) - Guillen, Jordi; Asche, Frank; Carvalho, Natacha; Fernández Polanco, José M.; Llorente, Ignacio; Nielsen, Rasmus; Nielsen, Max; Villasante, Sebastian
Abstract: Through its structural funds the European Union (EU) has invested €1.17 billion in the aquaculture sector over the period 2000–2014. In addition, the EU plans to spend a further €1.72 billion on the sector over the period 2014–2020 through the European Maritime and Fisheries Fund (EMFF). Despite this support, EU aquaculture production has not taken off. Indeed, EU production volume in 2016 was 8% less than in 2000, while global production increased by more than 150%. These investments aim to make the EU aquaculture sector more successful and competitive by focusing on quality, health and safety, as well as, eco-friendly production to provide consumers with high-quality, highly nutritional and trustworthy products. This study provides the first comprehensive overview on the allocation of the different structural funds in the aquaculture sector and across EU Member States from the year 2000–2020. The importance of these subsidies is put into perspective by comparing their evolution within and across the development of the different EU countries' aquaculture sectors.